Peran Orang Tua dalam Pembelajaran Daring di Sekolah Dasar - Pujiastuti Pujiastuti; Ayuhan Ayuhan (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2022)
This  research  was  motivated  by  curiosity  what  is  the  role  of  parents  when accompanying  children  to  do  chores  at  home  during  the  pandemic.  This study  aims  to  determine  (1)  the  role  of  parents  in  online  learning  at  SDN Kembangan Utara 09 Pagi Jakarta Barat, (2) Efforts by parents in increasing the seriousness of students in online learning at SDN Kembangan Utara 09 Pagi  Jakarta  Barat  and  (3)  the  obstacles  faced  faced  by  parents  in  online learning at SDN Kembangan Utara 09 Pagi, Jakarta Barat. The methodology of  this  research  is  qualitative.  The  subjects  in  this  study  were  parents  and homeroom teachers for grade II at SDN Kembangan Utara 09 Pagi, Jakarta Barat.  Data  collection  was  taken  through  interviews,  observation, documentation.  The  author  acts  as  a  direct  interviewer  to  collect  data through parents and second grade homeroom teachers. The results showed that (1) The role of parents in online learning at SDN Kembangan Utara 09 Pagi Jakarta Barat is to have three roles at once, namely the role of parents, breadwinners and teachers at home (2) The efforts of parents in increasing the seriousness of students in online learning at SDN Kembangan Utara 09 Pagi  Jakarta  Barat  is  to  provide  motivation,  guidance  and  assistance  (3) Obstacles faced by parents in online learning at SDN Kembangan Utara 09 Pagi  Jakarta  Barat  are  limited  infrastructure  facilities,  such  as  mobile phones, motivation, internet quota and time. Keywords : Parents, Online Learning and Motivation